KOMUNIKASI INTERPERSONAL DALAM PERSPEKTIF AL-QUR’AN (Studi Kritis Kisah Komunikasi Keluarga Ibrahim dalam Tafsȋr Ibnu Katsȋr) - Agam, Wahyu (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
This research discusses the Al-Qur'an as the source of all knowledge turns out to give a lot of value to the science of Islamic communication, the values of the Al-Qur'an that can be instilled in interpersonal communication are; (1) qaulan karȋmâ (words full of respect), (2) qaulan balȋghâ (words that are straightforward and effective), (3) qulan ma'rȗfâ (words that are kind and full of courtesy), (4) qaulan sadȋdâ (true words and not lies), (5) qaulan layyinâ (gentle words), and (6) qaulan maysȗrâ (words that are easy to understand). The method used in this research is: qualitative research method. This research is classified as a type of library research that focuses on the theme of